2007
DOI: 10.1152/ajpendo.00283.2006
|View full text |Cite
|
Sign up to set email alerts
|

Increased IRS-2 content and activation of IGF-I pathway contribute to enhance β-cell mass in fetuses from undernourished pregnant rats

Abstract: We have previously shown that fetuses from undernourished (U) pregnant rats exhibited an increased β-cell mass probably related to an enhanced IGF-I replicative response. Because IGF-I signaling pathways have been implicated in regulating β-cell growth, we investigated in this study the IGF-I transduction system in U fetuses. To this end, an in vitro model of primary fetal islets was developed to characterize glucose/IGF-I-mediated signaling that specially influences β-cell proliferation. We found that U fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…In this context, the lack of expression of IGF-2 has been associated with developmental apoptosis in the pancreatic islet cells of neonatal rat (Petrik et al 1998), whereas IGF-2 overexpression abolishes islet cell death (Hill et al 2000). Interestingly, we have found in the present study that undernutrition enhances pancreatic IGF-2 expression in neonates, in agreement with previous works that have reported nutritional upregulation of IGFs in pancreas under conditions of global food restriction , Fernández et al 2007, Gatford et al 2008. However, it contrasts with the effect of low-protein diet on the IGF axis, which induces a reduction in pancreatic IGF-2 expression (Petrik et al 1999).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this context, the lack of expression of IGF-2 has been associated with developmental apoptosis in the pancreatic islet cells of neonatal rat (Petrik et al 1998), whereas IGF-2 overexpression abolishes islet cell death (Hill et al 2000). Interestingly, we have found in the present study that undernutrition enhances pancreatic IGF-2 expression in neonates, in agreement with previous works that have reported nutritional upregulation of IGFs in pancreas under conditions of global food restriction , Fernández et al 2007, Gatford et al 2008. However, it contrasts with the effect of low-protein diet on the IGF axis, which induces a reduction in pancreatic IGF-2 expression (Petrik et al 1999).…”
Section: Discussionsupporting
confidence: 92%
“…We previously reported that protein-caloric food restriction (65% of ad libitum intake) applied during the last third of gestation caused an increase of b-cell mass in fetuses at term , associated to the stimulation of b-cell proliferation due to locally increased pancreatic IGF-1 and islet IRS-2 production , Fernández et al 2007. Nevertheless, food restriction continued after birth induced a decrease in b-cell mass at 4 days of life and this effect persisted until adult age .…”
Section: Introductionmentioning
confidence: 98%
“…A recent study described that fetal rat islets isolated from litters of undernourished mothers differed from islets from litters of control mothers, in regard to increased islet replication. This was coupled to an increased IRS2 protein content and an enhanced glucose/IGF-1 stimulation of the IRS2/PI3K/PKB pathway (Fernandez, et al 2007). From these reports, it is not possible to deduce if IRS2-signaling is strictly necessary for beta cell mass expansion during the embryonal development of the endocrine pancreas although signalling through IRS2 positively affects the beta cell mass.…”
Section: Discussionmentioning
confidence: 98%
“…Islet isolation and culture, and measurement of glucagon secretion and content Islets were isolated as previously described [19,21] (electronic supplementary material [ESM] Methods). Glucagon secretion was measured by RIA in isolated islets after exposure to different glucose concentrations (ESM Methods).…”
Section: Methodsmentioning
confidence: 99%